UNIMAS undergraduates' perceptions of group work for group assignments - Shirley, Michael Slee. (UNIMAS, 2009)
Group work has become one of the important instructional strategies in the higher education. This study aims to examine whether gender and race affect undergraduates’ perceptions of group work for group assignments and the role of instructor that students wish them to fulfill when doing their group assignments. The research objectives for this study are to find out UNIMAS undergraduates’ perceptions of group work for group assignments in terms of 1) their experiences, 2) usefulness, 3) preference of instructor roles, and lastly, 4) the influence of gender and race on their perception of usefulness and preferences instructor roles in doing group assignments. 200 students from five programmes in Faculty of Cognitive Sciences and Human Development participated in a survey questionnaire. The findings show that the majority of the students had positive perceptions towards group work for group assignments in terms of time spent and relationship with other group members. However, some students disliked group work for group assignments because of the difficulty to meet, domination of group members, and slackers. In addition, the results reveal that the students needed instructor’s assistance at the beginning and at the end of the group assignments. The recommendation for the future research is to lo ok in depth the complexities of grouping of race and gender in groups.